EDUCATION, BETWEEN SCIENCE AND TECHNIQUE - Rivera Piragauta, José Alberto (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This paper establishes a philosophical analysis towards education. It also pretends to be an approach even a disclosure by rediscove- ring the role of education while following specific coordinates such as science and technique, not forgetting the main focus on virtual education. Methodology was constituted of review and analysis of some of the texts quoted in this article, as potential ways to lead readers into interesting and trend topics on education. As topics are established, hypothesis in development would be: Technical object as meeting spot for science and technique justifying new education technology in online learning environments. As a fundamental consideration based on history richness of mankind thought and its endorsement to science and so to knowled- ge, only possible if it has its own replica in education field. Such reflection has a heavy load in philo- sophical literature, which may help as a foundation for elaborating a new lecture on education in today’s technological world, al- ready familiar for all humans. Last, for now our invitation to the reader in order to discover all edges and main ideas in order to give new approaches on the subject.